A CONTRASTIVE ANALYSIS OF SENTENCE STRUCTURE IN UZBEK, RUSSIAN, AND ENGLISH - Abduvakhobova Dilnoza Jorabekovna; Ashurov Alisher (TADQIQOTLAR, 2025)
Annotation: This article analyzes the structural differences in sentence construction among Uzbek, Russian, and English. It discusses the syntactic roles of sentence constituents, the order of elements, morphological markers, tense and aspect systems, and pragmatic nuances such as emphasis and intonation. The analysis is based on contrastive linguistic methods and explores how these languages utilize grammar and structure to express meaning. This comparative study aims to support theoretical linguistics and second language acquisition, especially for learners and educators working across these three linguistic systems.